Immune plasma for the treatment of severe influenza: an open-label, multicentre, phase 2 randomised study. Issue 6 (June 2017) - Beigel, John H; Tebas, Pablo; Elie-Turenne, Marie-Carmelle; Bajwa, Ednan; Bell, Todd E; Cairns, Charles B; Shoham, Shmuel; Deville, Jaime G; Feucht, Eric; Feinberg, Judith; Luke, Thomas; Raviprakash, Kanakatte; et al.
Summary: Background: Influenza causes substantial morbidity and mortality despite available treatments. Anecdotal reports suggest that plasma with high antibody titres to influenza might be of benefit in the treatment of severe influenza. Methods: In this randomised, open-label, multicentre, phase 2 trial, 29 academic medical centres in the USA assessed the safety and efficacy of anti-influenza plasma with haemagglutination inhibition antibody titres of 1:80 or more to the infecting strain. Hospitalised children and adults (including pregnant women) with severe influenza A or B (defined as the presence of hypoxia or tachypnoea) were randomly assigned to receive either two units (or paediatric equivalent) of anti-influenza plasma plus standard care, versus standard care alone, and were followed up for 28 days. The primary endpoint was time to normalisation of patients' respiratory status (respiratory rate of ≤20 breaths per min for adults or age-defined thresholds of 20–38 breaths per min for children) and a room air oxygen saturation of 93% or more. This study is registered withClinicalTrials.gov, numberNCT01052480 . Findings: Between Jan 13, 2011, and March 2, 2015, 113 participants were screened for eligibility and 98 were randomly assigned from 20 out of 29 participating sites. Of the participants with confirmed influenza (by PCR), 28 (67%) of 42 in the plasma plus standard care group normalised their respiratory status by day 28 compared with 24 (53%) of 45 participants on standard care alone (p=0·069). The hazard ratio (HR) comparing plasma plus standard care with standard care alone was 1·71 (95% CI 0·96–3·06). Six participants died, one (2%) from the plasma plus standard care group and five (10%) from the standard care group (HR 0·19 [95% CI 0·02–1·65], p=0·093). Participants in the plasma plus standard care group had non-significant reductions in days in hospital (median 6 days [IQR 4–16] vs 11 days [5–25], p=0·13) and days on mechanical ventilation (median 0 days [IQR 0–6] vs 3 days [0–14], p=0·14). Fewer plasma plus standard care participants had serious adverse events compared with standard care alone recipients (nine [20%] of 46 vs 20 [38%] of 52, p=0·041), the most frequent of which were acute respiratory distress syndrome (one [2%] vs two [4%] patients) and stroke (one [2%] vs two [4%] patients). Interpretation: Although there was no significant effect of plasma treatment on the primary endpoint, the treatment seemed safe and well tolerated. A phase 3 randomised trial is now underway to further assess this intervention. Funding: National Institute of Allergy and Infectious Diseases, US National Institutes of Health.